Acute exercise increases fibroblast growth factor 21 in metabolic organs and circulation. Issue 12 (22nd June 2016) - Tanimura, Yuko; Aoi, Wataru; Takanami, Yoshikazu; Kawai, Yukari; Mizushima, Katsura; Naito, Yuji; Yoshikawa, Toshikazu
Abstract: Fibroblast growth factor 21, a metabolic regulator, plays roles in lipolysis and glucose uptake in adipose tissues and skeletal muscles. Its expression in skeletal muscle is upregulated upon activation of the phosphatidylinositol 3‐kinase/Akt signaling pathway, which is induced by exercise and muscle contraction. We examined the increase of fibroblast growth factor 21 after acute exercise in metabolic organs, especially skeletal muscles and circulation. Participants exercised on bicycle ergometers for 60 min at 75% of their V ˙ O2 max. Venous blood samples were taken before exercise and immediately after exercise. In an animal study, male ICR mice were divided into sedentary and exercise groups. Mice in the exercise group performed treadmill exercises at 30 m min −1 for 60 min. Shortly thereafter, blood, liver, and skeletal muscle samples were taken from mice. Acute exercise induced the increase of serum fibroblast growth factor 21 in both humans and mice, and increased fibroblast growth factor 21 expression in the skeletal muscles and the liver of mice. Acute exercise activated Akt in mice skeletal muscle. Acute exercise increases fibroblast growth factor 21 concentrations in both serum and metabolic organs. Moreover, results show that acute exercise increased the expression of fibroblast growth factor 21 in skeletal muscle, accompanied by the phosphorylation of Akt in mice. Abstract : We examined the increase of fibroblast growth factor 21 after acute exercise in metabolic organs, especially skeletal muscles, and circulation. In conclusion, acute exercise increases fibroblast growth factor 21 concentrations in both serum and metabolic organs. Moreover, results show that acute exercise increased the expression of Fibroblast growth factor 21 in skeletal muscle, accompanied by the phosphorylation of Akt in mice.